Anthocyanins: Metabolic Digestion, Bioavailability, Therapeutic Effects, Current Pharmaceutical/Industrial Use, and Innovation Potential - Huseyin Ayvaz; Turgut Cabaroglu; Asiye Akyildiz; Cigdem Uysal Pala; Riza Temizkan; Erdal Ağçam; Zayde Ayvaz; Alessandra Durazzo; Massimo Lucarini; Rosa Direito; Zoriţa Diaconeasa (MDPI AG, 2022)
In this work, various concepts and features of anthocyanins have been comprehensively reviewed, taking the benefits of the scientific publications released mainly within the last five years. Within the paper, common topics such as anthocyanin chemistry and occurrence, including the biosynthesis of anthocyanins emphasizing the anthocyanin formation pathway, anthocyanin chemistry, and factors influencing the anthocyanins' stability, are covered in detail. By evaluating the recent in vitro and human experimental studies on the absorption and bioavailability of anthocyanins present in typical food and beverages, this review elucidates the significant variations in biokinetic parameters based on the model, anthocyanin source, and dose, allowing us to make basic assumptions about their bioavailability. Additionally, special attention is paid to other topics, such as the therapeutic effects of anthocyanins. Reviewing the recent in vitro, in vivo, and epidemiological studies on the therapeutic potential of anthocyanins against various diseases permits a demonstration of the promising efficacy of different anthocyanin sources at various levels, including the neuroprotective, cardioprotective, antidiabetic, antiobesity, and anticancer effects. Additionally, the studies on using plant-based anthocyanins as coloring food mediums are extensively investigated in this paper, revealing the successful use of anthocyanins in coloring various products, such as dietary and bakery products, mixes, juices, candies, beverages, ice cream, and jams. Lastly, the successful application of anthocyanins as prebiotic ingredients, the innovation potential of anthocyanins in industry, and sustainable sources of anthocyanins, including a quantitative research literature and database analysis, is performed.